Effect of Cash Conversion Cycle on the Profitability of Public Listed Insurance Companies - Nwude, E. Chuke; Agbo, Elias I.; Ibe-Lamberts, Christian (International Journal of Economics and Financial Issues, 2018)
Cash Conversion Cycle (CCC) constitutes a powerful metric for discovering how efficiently a company manages its working capital. A company that possesses low CCC is more efficient as it turns its working capital over many times in one year and allows it to generate more sales for the cash invested. This paper sets out to investigate the effect of CCC on the Return on Assets of selected Nigerian quoted insurance firms for the period (2000- 2011). The Return on Assets (ROA) is used as a measure of profitability. Data were collected from the annual financial reports of sampled insurance companies. Multiple regression technique was used in analyzing the model for testing the hypotheses. ROA was used as the dependent variable. While CCC was presented as the explanatory variable, Current Ratio, Debt Asset Ratio, Fixed Financial Total Asset Ratio, Growth and Size were all incorporated in the model as control variables. The results indicated that Cash Conversion Cycle had negative and significant effect on profitability. Based on the findings, the study recommends that Nigerian insurance companies should endeavour to reduce their number of days in Cash Conversion Cycle always in order to enhance their profitability. Keywords: Cash Conversion Cycle, Return on Assets, Working Capital, Profitability, Nigeria JEL Classifications: G2, G22